2008
DOI: 10.1371/journal.pone.0001755
|View full text |Cite
|
Sign up to set email alerts
|

DICER-LIKE2 Plays a Primary Role in Transitive Silencing of Transgenes in Arabidopsis

Abstract: Dicer-like (DCL) enzymes play a pivotal role in RNA silencing in plants, processing the long double-stranded RNA (dsRNA) that triggers silencing into the primary short interfering RNAs (siRNAs) that mediate it. The siRNA population can be augmented and silencing amplified via transitivity, an RNA-dependent RNA polymerase (RDR)-dependent pathway that uses the target RNA as substrate to generate secondary siRNAs. Here we report that Arabidopsis DCL2–but not DCL4-is required for transitivity in cell-autonomous, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
185
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 165 publications
(203 citation statements)
references
References 56 publications
12
185
1
1
Order By: Relevance
“…To try to reproduce that result, we used the same arf8-6 SALK line as in that study and crossed it to our established P1/HC-Pro transgenic Arabidopsis line (Mlotshwa et al, 2005(Mlotshwa et al, , 2008Endres et al, 2010). The P1/HC-Pro line is hemizygous for the turnip mosaic virus coding region, expresses high levels of the P1/HC-Pro mRNA, and has a severe developmental phenotype (Mlotshwa et al, 2005; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To try to reproduce that result, we used the same arf8-6 SALK line as in that study and crossed it to our established P1/HC-Pro transgenic Arabidopsis line (Mlotshwa et al, 2005(Mlotshwa et al, , 2008Endres et al, 2010). The P1/HC-Pro line is hemizygous for the turnip mosaic virus coding region, expresses high levels of the P1/HC-Pro mRNA, and has a severe developmental phenotype (Mlotshwa et al, 2005; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The paradoxical result was that the gel blot analysis in Figure 5E showed a total absence of CHS siRNAs in those plants, although Figure 5E also presented evidence that P1/HC-Pro was suppressing the hairpin transgene-induced posttranscriptional silencing. It has been well established, however, that primary siRNAs, such as those that would derive from the stem of a hairpin transgene, are not eliminated in P1/HC-Pro suppression of silencing (Johansen and Carrington, 2001;Mlotshwa et al, 2008;Zhang et al, 2008;Endres et al, 2010). Therefore, CHS siRNAs should have been present if P1/HC-Pro suppression of silencing was truly occurring, and their absence strongly suggested that some confounding factor had affected the Jay et al (2011) P1/HC-Pro studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations